The Effect of Unproductive and Productive Chicken Ratio on the Feasibility of Laying Hens Business - Muhammad Nur Hasan; Nining Haryuni; Lestariningsih Lestariningsih (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2023)
This study was conducted to determine the effect of unproductive and productive chickens ratio on the feasibility of laying hens business. This research was conducted in April – May 2022 in Kademangan District, Blitar Regency, East Java Province. This research is quantitative research and respondents in this study were 89 chicken farmers in Kademangan District, Blitar Regency, East Java Province. The material used in this research is primary and secondary data. The data obtained from the study were analyzed using interference analysis with a correlation test to determine the relationship between the dependent variable and the independent variable. Based on the results of statistical analysis, it was found that 40.91% of the respondents only had egg-laying chickens; 32.95% of respondents have layer and grower chickens; 22.73% of respondents have layer and starter chickens; and 3.41% of respondents have layer, grower and starter chickens. The ratio of unproductive chickens to productive chickens has a very strong effect on increasing production costs, decreasing profits, increasing BEP and decreasing R/C and having a strong effect on decreasing revenue with a correlation interval of 0.9461, respectively; -0.8772; 0.9727; -0.8818 and -0.7712. It can be concluded that the ratio of unproductive chickens to productive chickens has a very strong effect on the feasibility of laying hens business with an average R/C value of 1.14.